Powers and Prospects : Reflections on Human Nature and the Social Order - Chomsky, Noam (London Pluto Press, 2016)
An eclectic collection of Chomsky's writings on subjects ranging from East Timor and the Middle East to linguistics and social policy.
Include Index
Keywords: World politics -- Language and languages--Philosophy -- Philosophical anthropology